Knowledge in sustainable development:from forms of knowledge to knowledge processes - TOVEY, HILARY (Blackwell, 2008)
Lack of data or empirical information, insecurity about scientific knowledge, and disputes on how to manage knowledge, emerge as central concerns when we study changes in rural development under the influence of sustainability discourses. In this synthesis we summarize and interpret results from the CORASON project for sustainable resource management, within both policy discourses and the local realities of rural development projects. We identify a variety of operational variants for sustainable development in these projects: the understanding of sustainable development found in rural development practice is more manifold and pluralistic, less standardised than in the policy programmes that guide it, and also critical of some premises of these programmes. From the knowledge forms and ideas entering rural development practices emerges a model of rural sustainable development which is less hierarchic and hegemonic, and comes more from the target groups, beneficiaries and local populations than the actors in the policy process and scientific discourses. It requires more in-depth study of knowledge interaction in resource management. To describe the emerging ideas of knowledge practices we use the concepts of situated and relational knowledge, formulated in recent epistemological studies but not yet systematically introduced in the analysis of rural development processes.
PUBLISHED
Keywords: sustainable rural development; knowledge management; resource management